Le cerf chez les anciens P’urhépecha du Michoacan (Mexique) : guerre, chasse et sacrifice - Brigitte Faugère (Journal de la Société des Américanistes)
The deer among the ancient P’urhépecha of Michoacan, Mexico : war, hunting and sacrifice. The study of the place of deers in the Relación de Michoacán and in archaeological remains shows the importance of this animal in ancient Pur’hépecha’s mythology. The deer of this region (Odocoileus virginianus) plays a relevant part in the rituals because his capture can be assimilated to a war ending with sacrifices. Within the mythology, it is associated with the sun, when it is regenerating before rising in the east. The deer plays also a particular role for the elite of the 16th century, because it was chosen by the dominant warriors group as an emblematic animal.